Evaluating locally sourced inert dusts as insecticides against the cereal leaf beetle (Oulema melanopus [L.]; Coleoptera: Chrysomelidae): a combined laboratory and field study - Luka Batistič; Filip Vučajnk; Matej Vidrih; Aleksander Horvat; Iztok Jože Košir; Urban Šilc; Tanja Bohinc; Stanislav Trdan (Cogent Food & Agriculture)
The Cereal Leaf Beetle (CLB), Oulema melanopus [L.], poses a major threat to wheat (Triticum aestivum L.) production, worsened by insecticide resistance and changing EU pesticide regulations. In 2023, we conducted laboratory and field trials to evaluate five inert dusts (diatomaceous earth, quartz sand, Ailanthus altissima dust, Norway spruce wood ash, and zeolite) against all CLB life stages. We assessed pest abundance, wheat damage index, wheat yield, and grain quality. In the lab, diatomaceous earth was highly effective (96%–100%), followed by Norway spruce wood ash (70.4%–96.7%). Field efficacy was hampered by wet weather, affecting dust applications, although the positive control was effective except against CLB eggs. By the last sampling date, damage indices for diatomaceous earth, A. altissima dust, and wood ash treatments ranged from 3.87 to 4.12, lower than the negative control (4.75 ± 0.02) but higher than the positive control (2.88 ± 0.35). Wheat yield was consistent across all treatments (∼5 tons), except for the negative control (4.2 ± 0.86 tons) and A. altissima dust (3.9 ± 0.47 tons). Grain quality showed no significant differences. Our study highlights the potential of various inert dusts against CLB, though wet weather limits their field effectiveness, requiring more applications. Further research is needed to develop practical, sustainable CLB management strategies.